Proses Adaptasi Mahasiswa Binus University Asal Daerah - Tukina, Tukina (Bina Nusantara University, 2014)
Research on the adaptation process of students from other regions aim to answer fundamental things related to the adaptation process of students from other regions who are studying at Binus University. Appropriate adaptation process can help create conducive environment to achieve good quality of learning (good quality of education). With good adaptability, students are expected to graduate well too. Becoming excellent graduates are the dream of every student, parents and university as well as community and country. Research of adaptation process of students from other regions who are studying at Binus University was conducted with descriptive qualitative methodology, the data obtained through in-depth interviews in the field and then were exposed to inductive analysis through the stages planned. To support the study, data collection is done in the following way: observation, survey, search and find key informants, and conducted in-depth interviews. Once the data is collected and analyzed then the next step is to generate data on the final results report. Students who come from other regions view that the process of adaptation is important and should be done. What is important and should be done in an adaptation process includes several things, such as the distance between students’ new area of domicile to campus, social culture in students’ place of origin to the students’ new area of domicile, and the situation of environmental conditions (society) of students’ place of origin to students’ new domicile as well as individual specific views (attitudes and behaviors ). Students from other regions adapt in a variety of ways, ranging from respecting new area of domicile custom, getting involved in students’ activities in campus and to comply with regulations. Adaptation also needs to be done to the entire academic community, including with other related environment. From the results of the study also showed that students who come from other regions view adaptation process is associated with learning outcomes at the university.